The Influence of Audit Fee, Audit Tenure, Auditor Rotation, and Company Size on Audit Quality of Banking Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period - Solin, Yosefa Pebe Karina; Banurea, Wina Marliana; Teng, Sauh Hwee; Piter, Jhon (International Journal Of Economics Social And Technology (IJEST), 2025)
The purpose of this study is to examine and evaluate the impact of audit fees, audit tenure, audit rotation, and corporate consistency on audit credibility within the banking corporations listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sampling method used in this study is purposive sampling, utilizing financial summary data from banking industry corporations listed on the IDX during the specified period. The regression data interpretation indicates that audit fees, audit rotation, and audit credibility significantly influence perceptions of audit credibility. However, the engagement between auditor and client does not significantly affect perceptions of audit credibility. Accordingly, large companies with high audit fees and regular audit rotation tend to influence the quality of audits, either positively or negatively.